2022
DOI: 10.1590/fst.61821
|View full text |Cite
|
Sign up to set email alerts
|

METRNL reduced inflammation in sepsis-induced renal injury via PPARδ-dependent pathways

Abstract: Materials and methods Arthritis model studiesEight-week-old male C57BL/6 mice were housed separately under controlled temperature (22 ± 3 °C), 50 ± 20% humidity, light-dark cycle of 12 h and free access to food and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Liu et al (2019) also showed an inverse association between Metrnl level and hs-CRP in 193 patients with coronary artery disease. In their study, Hu et al (2021) showed that Metrnl injection in mice models with sepsis reduced the inflammatory biomarkers of IL-6, IL-4, IL-1b and TNF-a, and increased IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2019) also showed an inverse association between Metrnl level and hs-CRP in 193 patients with coronary artery disease. In their study, Hu et al (2021) showed that Metrnl injection in mice models with sepsis reduced the inflammatory biomarkers of IL-6, IL-4, IL-1b and TNF-a, and increased IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of peroxisome proliferator-activated receptor-delta (PPAR-δ) pathways is another anti-inflammatory function of Metrnl. Metrnl enhances the gene expression of PPAR-δ (Jung et al , 2018) which, as a member of the PPARs family, induces apoptosis and decreases inflammation through the downregulation of the gene expression of matrix metalloproteinase-9, inducible nitric oxide synthase and scavenger type A receptors in macrophages and prevents the expression of IL-1β and IL-6 in monocytes (Hu et al , 2021). In addition to the energy hemostasis of PPAR-δ, the anti-inflammatory effect also occurs by way of the induction of adenosine monophosphate-activated protein kinase activity which suppresses the Nuclear factor kappa-light-chain-enhancer of activated B cells signaling pathway and inhibits aggregation of reactive oxygen species (Ding et al , 2006; Salminen et al , 2011).…”
Section: Discussionmentioning
confidence: 99%